Association between diabetic retinopathy and serum lipoproteins level - Shakya, K; Shrestha, JK; Joshi, SN (Nepalese Journal of Ophthalmology, 2010)
Introduction: Diabetic retinopathy is the leading cause of blindness of working-age patients in the urban areas. Objective: To find out the association between diabetic retinopathy and serum lipoproteins in patients with diabetes mellitus Materials and methods: A community-based cross-sectional study involving 100 subjects with type II diabetes living in the cities of Kathmandu, Bhaktapur and Lalitpur of Nepal was carried out using a purposive sampling method. The retinopathy was classified according to the modified Airlie House classification of diabetic retinopathy. The patients with systolic hypertension were excluded. The blood sugar level was assessed by using glycosylated hemoglobin. The fasting serum lipoproteins were assessed by photometric enzymatic methods. Statistics: The SPSS version 10.0 software was used. The p value of <0.05 was considered significant. Results: The majority (n=91) of the patients were in the age group 31-60 years with the mean of 48.2 ± 9.5. The mean duration of diabetes mellitus in the patients with no-diabetic-retinopathy was 4 ±3.4 years and that in those with the retinopathy was 6.4 ± 4years, (p =0.006). The mean glycosylated hemoglobin level for no-diabetic-retinopathy group was 6.9 ±1.1 %, whereas for the diabetic retinopathy group, it was 7.7 ± 1.5% (p = 0.004). The mean values of serum lipoproteins when taken together were slightly higher in the diabetic retinopathy group than in the group with no-diabetic-retinopathy. The serum triglyceride value was higher in the group with diabetic retinopathy than in the group with no retinopathy. Serum triglyceride had a low degree of positive correlation with HbA1c value. Conclusion: There is no significant association between the serum lipoprotein levels and diabetic retinopathy in patients with type II diabetes mellitus. Serum triglyceride level has a low degree of positive correlation with HbA1c value. Keywords: diabetic retinopathy; lipoproteins; glycosylated hemoglobin DOI: 10.3126/nepjoph.v1i2.3684 Nep J Oph 2009;1(2):107-113